Likely future extirpation of another Asian river dolphin: The critically endangered population of the Irrawaddy dolphin in the Mekong River is small and declining. Issue 3 (18th October 2012) - Beasley, I.; Pollock, K.; Jefferson, T. A.; Arnold, P.; Morse, L.; Yim, S.; Lor Kim, S.; Marsh, H.
Abstract The population of Irrawaddy dolphins that occupies the Mekong River in southern Lao People's Democratic Republic and Cambodia is classified as Critically Endangered by the IUCN. Based on capture‐recapture of photo‐identified individuals, we estimated that the total population numbered 93 ± SE 3.90 individuals (95% CI 86–101), as of April 2007. The combined photo‐identification and carcass recovery program undertaken from 2001 to 2007 established that the Irrawaddy dolphin population inhabiting the Mekong River has reached a critical point with regards to its continued survival, where immediate research and management actions are required to greatly reduce adult mortality, and establish the cause of newborn mortality. In addition, community consultation is required to initiate, and evaluate, urgently required conservation measures. An ongoing well‐designed combined program of abundance estimation (i.e., photo‐identification) and carcass recovery is required to monitor total population size and mortality rates, to inform and evaluate management initiatives. The conclusions of this paper are likely generic to river dolphin populations, particularly where photo‐identification is possible.